Adhesion loss mechanism based on carboxymethyl cellulose-filled hydrocolloid dressings in physiological wounds environment. (1st May 2020) - Kong, Denan; Zhang, Qunchao; You, Jun; Cheng, Yuanyuan; Hong, Cheng; Chen, Zihe; Jiang, Tao; Hao, Tonghui
Graphical abstract: Adhesion loss of hydrocolloid wound dressings, ubiquitous clinical problem, can be explained by dramatic increasing surface energy due to the dissolution, swelling and exudation of hydrophilic fillers. Highlights: The adhesion loss mechanism was explored based on adhesion mechanism. Hydrophilic fillers absorbed moisture, dissolved and effused under wet environment. The effused fillers covered dressing surface, causing the decrease in adhesion. Dramatic increasing surface energy was the main reason for adhesion loss. Abstract: Adhesion loss of hydrocolloid wound dressings is ubiquitous clinical problem, which seriously reduces the therapeutic efficiency and patient experience. In order to address this problem, the clarification on adhesion loss mechanism and the development of effective alternatives of commercial hydrocolloid dressings are urgent and inevitable. Herein, adhesion loss mechanism of hydrocolloid dressings was investigated using sodium carboxymethyl cellulose (CMC)-filled hydrocolloid dressings exposing to physiological environment as model. The adhesion mechanism and contact angle tests were combined to obtain surface energy of dressings. The results indicated that the dissolution, swelling and exudation of CMC occurred successively (concentration reached 1.607 g/L after 10 h). The effused CMC led to the dramatic increase in surface energy (from 14.5–80.7 mN/m) and adhesion loss appeared. This work explored the origin of adhesion loss of hydrocolloid wound dressings and might promote the designing of hydrocolloid dressings with both excellent humidity control and sustained self-adhesiveness.